Effects of periodontal treatment on CRP and other cellular markers in blood = Efecto del tratamiento periodontal en la PCR y otros marcadores celulares en sangre - Rojas González, Gisella 1969- (2025)
Periodontitis is a chronic inflammatory disease that affects public health worldwide. It has been related to microorganisms that trigger an inflammatory response that, in turn, produces a deterioration of the teeth's supporting tissue. In recent years, studies have shown some similarity and association between periodontitis and atherosclerotic cardiovascular disease. The serum increases in C-reactive protein (CRP), fibrinogen, alpha-1 antitrypsin, moderate increase in leukocytes, increase in sedimentation rate and Von Willebrand factor antigen make it likely that there is a relationship between periodontal disease and other systemic conditions, specifically atherosclerotic disease. This study seeks to establish if there is any relationship between these values after phase II periodontal treatment in patients with periodontitis at the Faculty of Dentistry of the University of Costa Rica. The initial values are found in a previous publication (1). In this second stage, the sample was reduced to 14 patients, of whom 57% presented metabolic compromise such as rheumatoid arthritis, arterial hypertension and diabetes mellitus, and 50% decreased PCR levels. As for the mean level of the total sample, in both stages of the study, PCR increased from 2.72 (SD: 2.25) to 5.36 (SD: 9.68). Of the patients who received periodontal treatment, 21.4% had low PCR levels (<1 mg/L), 50% medium (1-3 mg/L) and 28.6% high (>3 mg/L). There was no statistically significant difference in any of the variables analyzed for cholesterol, triglycerides and fibrinogen. Of the total number of patients in whom carotid ultrasound was performed, 52.4% were diagnosed as healthy, 33.3% had bulbar myointimal hyperplasia and 14.3% had atheromatous plaques. One of the participants died of myocardial infarction. This study does not conclude that there is a relationship between periodontal disease and cellular markers, which are also found in atheromatous disease, but it can be affirmed...
La periodontitis es una enfermedad inflamatoria crónica que afecta la salud pública a nivel mundial. Ha sido relacionada con microorganismos que desencadenan una respuesta inflamatoria que, a su vez, produce un deterioro del tejido de soporte de los dientes. En los últimos años, se han realizado estudios que señalan cierta similitud y asociación entre la periodontitis y la enfermedad cardiovascular aterosclerótica. El aumento sérico de la proteína C reactiva (PCR), el fibrinógeno, la alfa-1 antitripsina, el aumento moderado de leucocitos, el incremento en la velocidad de sedimentación y del antígeno del factor de Von Willebrand hacen probable que exista relación entre la enfermedad periodontal y otros padecimientos sistémicos, específicamente la aterosclerótica. Este estudio busca establecer si existe algún tipo de relación entre estos valores después del tratamiento periodontal de fase II en pacientes con periodontitis de la Facultad de Odontología de la Universidad de Costa Rica. Los valores iniciales se encuentran en una publicación previa (1). En esta segunda etapa, la muestra se redujo a 14 pacientes, de los cuales el 57 % presentó compromiso metabólico como artritis reumatoidea, HTA y diabetes mellitus, y el 50 % disminuyó los niveles de PCR. En cuanto al nivel promedio de la muestra total, en ambas etapas del estudio, la PCR aumentó de 2,72 (DS: 2,25) a 5,36 (DS: 9,68). El 21,4 % de los pacientes que recibieron el tratamiento periodontal presentó niveles bajos de PCR (< a 1 mg/L), un 50 % medios (1-3 mg/L) y el otro 28,6 % elevados (> a 3 mg/L). No hubo una diferencia estadísticamente significativa en ninguna de las variables analizadas en función de colesterol, triglicéridos y fibrinógeno. Del total de pacientes en los que se realizó el ultrasonido de carótidas, el 52,4 % fue diagnosticado como sano, el 33,3 % presentó hiperplasia miointimal bulbar y el 14,3 % placas ateromatosas. Uno de los participantes...
En revista Odóvtos, Online First, 2025
Descripción basada en el contenido visto el 19 de marzo, 2025
También disponible en formato HTML y EPUB